Análisis de la saturación de los puertos de la red gpon de la compañía CNT ubicada en la parroquia Barreiro Viejo - Díaz Sánchez, Mary Elizabeth (2019)
The present case study entitled Saturation Analysis of the GPON network ports of the company cnt of the old parish barreriro. The reason to carry out this study is to know the possible saturations of the ports because the CNT company before made the distribution of copper network and now with the renewed technology of the gpon network for which it made its change throughout the province. This new gpon network technology is distributed in the old Barreiro parish in which saturation has been presented by the capacity of clients that the parish presents as this network makes its transmission from the OLT (optical line terminal), attaches the ONT (Optical Network Terminal)